Direito à desconexão do trabalho como instrumento de proteção à saúde do trabalhador - Braga, Eduardo Souza [UNESP] (2015)
In contemporary society, taken over by advanced technique, the right to disconnect, the right to non-work, are important instruments for the preservation of workers' occupational health. The changes in the types of services provisions in the workplace or elsewhere, due to the opportunities offered by modern techniques, tend to render the worker constantly connected to his work in detriment of his private life. The dangerous confusion between personal and professional life can cause physical and mental illnesses. The fundamental right of workers not to work during their moments of rest, relaxation, and family time has, in this context, utmost importance and must be respected by all, including the government and the private sector. Since modern technique acts as a kind of facilitator when it comes to the increasing exploitation of human beings in the workplace, it is also through it that we must seek ways to prevent the ever increasing exploitation of workers. The technique which allows constant work at all times, should also act as a way to prevent it. Changes in attitude, particularly when it comes to the employer, given the technical innovations, are absolutely necessary to safeguard a person's right to disconnect herself from work. The effective respect of the workers' non-specific right to disconnect from their job depends on the actions of all parts involved, spontaneously or not. Only through the effective disconnection from work is that we are able to speak of a worker's full personality development in his path to become a social and cultural being.